Frailty assessment instruments: Systematic characterization of the uses and contexts of highly-cited instruments - Buta, Brian J. (Ageing Res Rev, 2015)
The medical syndrome of frailty is widely recognized, yet debate remains over how best to measure it in clinical and research settings. This study reviewed the frailty-related research literature by (a) comprehensively cataloging the wide array of instruments that have been utilized to measure frailty, and (b) systematically categorizing the different purposes and contexts of use for frailty instruments frequently cited in the research literature. We identified 67 frailty instruments total; of these, nine were highly-cited (≥200 citations). We randomly sampled and reviewed 545 English-language articles citing at least one highly-cited instrument. We estimated the total number of uses, and classified use into eight categories: risk assessment for adverse health outcomes (31% of all uses); etiological studies of frailty (22%); methodology studies (14%); biomarker studies (12%); inclusion/exclusion criteria (10%); estimating prevalence as primary goal (5%); clinical decision-making (2%); and interventional targeting (2%). The most common assessment context was observational studies of older community-dwelling adults. Physical Frailty Phenotype was the most used frailty instrument in the research literature, followed by the Deficit Accumulation Index and the Vulnerable Elders Survey. This study provides an empirical evaluation of the current uses of frailty instruments, which may be important to consider when selecting instruments for clinical or research purposes. We recommend careful consideration in the selection of a frailty instrument based on the intended purpose, domains captured, and how the instrument has been used in the past. Continued efforts are needed to study the validity and feasibility of these instruments.